Pengembangan Alat Peraga Valorem Fractus untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Pecahan Senilai - Agrestian, Rizki; Nurhikmayati, Iik (Papanda Journal of Mathematics and Science Research, 2024)
This research aims to develop mathematical teaching aids based on development models with a focus on Equivalent Fractions material. MTs Nurul Hikmah Cigasong School is faced with limited resources and mathematics learning media, which results in low student interest and motivation to learn. Mathematics education in Indonesia still shows low quality compared to other countries. Therefore, this research was carried out to create the "Valorem Fractus" teaching aid as an innovative solution to increase students' understanding of concepts in Equivalent Fractions material. The research method used is Research and Development, with stages of definition, design, and development. The trial was carried out at MTs Nurul Hikmah Cigasong, involving 18 class VII students as research subjects. The results of media and material validation tests by validators show a very high level of validity, with an average percentage of 94% and 95% respectively. The overall product validation test results show a validity level of 95%, confirming that the teaching aids and materials developed meet the expected validity standards. The use of Valorem Fractus teaching aids significantly increases students' understanding of concepts in Equivalent Fractions material. The implications of this research include recommendations for using Valorem Fractus teaching aids in mathematics learning, especially in Equivalent Fractions material. This research makes a positive contribution to the development of learning methods and teaching aids, motivates students with interactive and visual approaches, and improves negative perceptions of mathematics. Thus, the Valorem Fractus teaching aid can be relied on as an effective learning resource to improve students' understanding of concepts in Equivalent Fractions material.